Double dissociations in reading comprehension difficulties among Chinese–English bilinguals and their association with tone awareness. (23rd June 2016) - Choi, William; Tong, Xiuli; Deacon, S. Hélène
Abstract : Poor comprehenders have reading comprehension difficulties but normal word recognition ability. Here, we report the first study, which investigated (i) the dissociation and (ii) the prevalence of L1–L2 reading comprehension difficulties, and (iii) the levels of key metalinguistic skills in poor comprehenders among Chinese‐English bilingual children. From a sample of 124 Chinese–English second graders, we identified 18 poor comprehenders (six Chinese, six English, and six in both Chinese and English). We matched these with six average comprehenders of comparable age and word reading abilities. Multivariate analysis of covariance and univariate F tests revealed that poor Chinese comprehenders and poor English comprehenders had significantly lower levels of Chinese lexical tone awareness than average readers even after controlling for nonverbal intelligence. No significant differences emerged on scores for segmental phonological awareness and vocabulary knowledge, either in Chinese and English or on English lexical stress sensitivity. These findings were discussed in relation to the universal view of reading, cross language prosodic transfer and the simple view of reading.